Factors associated with influenza-like illness in care homes in Cheshire and Merseyside during the 2017–2018 influenza season. (October 2020) - Halloran, N.F.; Harries, A.D.; Ghebrehewet, S.; Cleary, P.
Abstract: Objectives: The aim of the study was to identify care home characteristics associated with reported care home influenza outbreaks and factors associated with increased transmission of influenza-like illness (ILI) in care homes in Cheshire and Merseyside during the 2017–2018 influenza season. Study design: This is a matched case-control study comparing characteristics between care homes with and without a declared influenza outbreak and a retrospective risk factor analysis of care home residents with ILI. Methods: Routinely collected outbreak surveillance data on symptomatic residents and staff, antiviral prophylaxis and influenza vaccination history, which were reported to Public Health England, were extracted from health protection electronic records. Further care home characteristics were extracted from the Care Quality Commission (CQC) website. Care homes with declared influenza outbreaks were matched with care homes without outbreaks. Chi-squared tests and logistic regression were used to examine associations between care home factors and ILI. Results: There were no significant differences in characteristics between 77 care homes with declared influenza outbreaks and 77 matched care homes without outbreaks. Of 2, 744 residents from the homes with a declared outbreak, 644 (24%) developed an ILI. The care home risk factors were having a low CQC score and activation of antiviral prophylaxis and the protective factors were having higher numbers of residents, specializing in dementia care and having the highest CQC score. Significantly more cases occurred in residential homes than in nursing homes, in homes with lower CQC scores and in homes where eligible residents were given antiviral prophylaxis. Conclusions: In homes with declared outbreaks, certain characteristics including activation of antiviral prophylaxis were associated with an increased risk of ILI. Further research is needed, particularly focussing on temporality between provision of prophylactic antivirals and the onset of ILI. Highlights: Homes with and without declared influenza outbreaks had similar characteristics. One in four residents from homes with declared outbreaks had influenza-like illness. Low Care Quality Commission (CQC) scores and antiviral prophylaxis were associated with more influenza. More data are needed on the timing of antiviral prophylaxis administration and cases. Protective factors included large homes, high CQC scores and dementia specialism.